ROLE OF TAX CONSULTANTS IN ENCOURAGING CORPORATE TAXPAYER COMPLIANCE WITH THE CORETAX ADMINISTRATION SYSTEM AS A MODERATING VARIABLE - Erlina Dwi Novitasari; Ilyona Risty (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study investigates the effect of the role of Tax Consultants on Corporate Taxpayer Compliance by examining the Coretax Administration System as a moderating variable during its implementation in 2025. The year 2025 marks a transitional period in the digitalization of tax administration aimed at strengthening sustainable tax governance. Tax compliance plays a vital role in maintaining state revenue stability to support sustainable social, economic, and environmental development. This research employs a quantitative approach with a sample of 86 corporate taxpayers who receive professional assistance from tax consultants in fulfilling their tax obligations and have utilized the Coretax system throughout 2025. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4 to assess the measurement model, structural relationships, and research hypotheses. The findings reveal that the role of Tax Consultants has a positive and statistically significant effect on Corporate Taxpayer Compliance. However, the Coretax Administration System does not exhibit a significant moderating effect on the relationship between Tax Consultants and Corporate Taxpayer Compliance. These results indicate that professional assistance provided by Tax Consultants remains a key determinant in enhancing corporate taxpayer compliance despite ongoing changes in the tax administration system.